Formulation Variations and Antioxidant Efficacy of Red Sesbania Flowers (Sesbania grandiflora L.) as Herbal Tea - Sylvia, Diana; Hidayati, Fitri; Nita Rusdiana; Sefi Megawati (Universitas Muhammadiyah Yogyakarta, 2026)
Red sesbania flowers (Sesbania grandiflora L) are rich in bioactive compounds, particularly flavonoids, anthocyanins, and vitamin C, which play an important role as natural antioxidants. In the development of functional beverages, red sesbania flowers have significant potential for use in herbal tea processing. The combination of cinnamon (Cinnamomum burmanni), which contains cinnamaldehyde and phenolic compounds, enhances aroma and flavor while also strengthening both its anti-inflammatory and antioxidant effects. This study aims to formulate a tea product made from red sesbania flowers with a combination of cinnamon and mint leaves in accordance with SNI quality standards and to evaluate its antioxidant activity. The research was conducted in several stages, including the preparation of herbal tea from red sesbania flowers, the addition of cinnamon and mint leaves, hedonic tests, SNI quality tests (organoleptic, water content, ash content, and total polyphenol content), and analysis of antioxidant activity. The results showed that the best formula for red sesbania flower tea was the one with the addition of 15% cinnamon and 20% mint leaves. The antioxidant activity of these teas was relatively weak, with IC50 values of 472.335 µg/mL for the original tea, 206.93 µg/mL for the cinnamon formula, and 525.825 µg/mL for the mint formula. Red sesbania flower herbal tea exhibited weaker antioxidant activity than vitamin C, with a significantly higher IC50 value (1.88 µg/mL) compared to vitamin C.